Synthesis of asymmetrically dihydrophobic chain poly(ethylene glycol) lipids for long circulation and membrane fusion. Issue 5 (30th May 2022) - Zhao, Yu; Liu, Chenyu; Chen, Hailiang; Zhou, Hengjun; Yu, Simiao; Mi, Deze; Yue, Shuli; Qiao, Weihong
Abstract: Liposomes are the predominant drug delivery system widely used in the pharmaceutical industry, but rapid clearance and endosome degradation are the main barriers to improve the delivery efficiency of liposomes, especially for protein or genes. Simulating viral membrane fusion peptides, four asymmetrically dihydrophobic chain polyethylene glycol (PEG) lipids with long circulating and membrane fusion properties have been designed and synthesized with a high yield. The structure of synthetic PEG lipids is characterized by 1 H NMR and mass spectrometry. The critical micelle concentrations of PEG lipids are lower by one or two orders of magnitude compared with traditional surfactants such as SDBS or SDS, which show excellent self‐assembly performance of lipids. The size and morphology of liposomes constituted with neutral lipid DOPC and PEG lipid are characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM). In the conditions of 50% ethanol and 5–25 mmol L −1 Ca 2+, the PEG neutral lipid complexes encapsulated pEGFP are almost neutral with a diameter below 300 nm.